2018
DOI: 10.18203/2320-1770.ijrcog20180165
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric near miss events and maternal deaths in a tertiary care hospital

Abstract: Background: Maternal mortality is one of the important indicators of maternal health. Objectives of present study were to determine the frequency of maternal near miss, maternal near miss incidence ratio, maternal near miss to mortality ratio and mortality index and to study the risk factors associated with near miss events.Methods: A retrospective analysis of severe maternal morbidity from January 2015 to December 2015 was studied. Data was collected from women with pregnancy related life-threatening complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The study by Patil V showed severe preeclampsia being risk factor in 54.4%, eclampsia in 6%, antepartum hemorrhage in 7.73% and postpartum hemorrhage in 7.56% of their cases, 3 cases had rupture uterus as risk factors. 15 The study done by Appinabhavi A, showed that 8 patients had hepatic encephalopathy, 9 patients had acute lung injury, 22 patients had MODS as complications. 16…”
Section: Discussionmentioning
confidence: 99%
“…The study by Patil V showed severe preeclampsia being risk factor in 54.4%, eclampsia in 6%, antepartum hemorrhage in 7.73% and postpartum hemorrhage in 7.56% of their cases, 3 cases had rupture uterus as risk factors. 15 The study done by Appinabhavi A, showed that 8 patients had hepatic encephalopathy, 9 patients had acute lung injury, 22 patients had MODS as complications. 16…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using Epi-info statistical package, version 3.3 with power 80% value of 2.5%, is chosen as the acceptable limit of precision (D) at a 95% level of confidence (CI), with expected prevalence 50% and worst acceptable 16%. Pilot study A pilot study was carried out before starting data collection on 10% of nurses (15) in order to test the clarity and applicability of including questions and statement content, feasibility, and consistency of the tool to detect any ambiguity in the study tools. The pilot study also served to estimate the time required to fill the form.there was no modification in the tool and the pilot study was included in the sample.…”
Section: Research Questionsmentioning
confidence: 99%